Aux marges de l'emploi: parcours de travailleuses domestiques québécoises, 1950-2000 - Charron, Catherine (Les éditions du remue-ménage, 2018)
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; his4550; histoire; justice sociale; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; thématiques; travail; travail domestique

Ogimah Ikwe: Native Women and Their Path to Leadership - Lajimodiere, Denise K. (Wicazo Sa Review, 2011)
Much documentation gathered on Native American women's activities originated in the journals of European male missionaries and explorers. These first visitors observed Native societies through the eyes of their own culture, a culture in which male activities were the only happenings of note. 1 This bias led to indirect and distorted descriptions of Native American women's activities and beliefs. 2 Scholars who study Native American women today have made significant inroads into their histories; however, many interpretations remain incorrect and undeveloped. Devon Mihesuah states, "Because many authors write from a patriarchal or white feminist perspective, the value of Indian women is vastly underrated." 3 Gretchen Bataille and Kathleen Sands address this shortcoming, saying, "The portrayal of American Indian women in North America over the last four centuries offers an uneven body of documentary evidence about the lives of Native women as individuals and members of their group." This study's purpose is to increase the visibility of Native American women in leadership roles by recording the voices and histories of nine Native American women leaders. It focuses on the experiences, perceptions, and beliefs of the women interviewed, giving a voice to nine of today's Native American female leaders, nine Ogimah Ikwe (leader women).
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; cours; discipline; discours dominant; femmes* au pouvoir; femmes* autochtones; féminisme autochtone; histoire et politique; patriarcat; pol4105; premier cycle; premières nations; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences de l'éducation; système colonial; systèmes d'oppressions; thématiques; travail; états-unis